Phosphorus Availability In Turfgrass Root Zones After Applications of Organic and Synthetic Nitrogen Fertilizers. Issue 1 (25th March 2013) - Stahnke, Gwen K.; Miltner, E. D.; Cogger, C. G.; Luchterhand, R. A.; Bembenek, R. E.
Abstract : Organic fertilizers have increased in popularity over the past ten years due to the belief they are more environmentally sound to use than synthetic fertilizers. Most fertilizers derived from organic materials contain phosphorus as well as nitrogen, so use may be affected in states that legislate the application of P to lawns. States are considering exempting organic fertilizers from their zero‐P legislation, as Wisconsin did, because it is thought that P from organic sources is less likely to be lost in leachate or runoff. Fertilizers are applied on turfgrasses as needed based on N form and content. Many organic fertilizers contain as much P as N in their formulations, and therefore similar amounts of P and N are applied with each application. Soil tests in native soil and a fairway sand and peat mix used in the Pacific Northwest showed that organic fertilizers applied at rates to provide adequate N for acceptable turf increased soil Bray‐1 P levels from 16 to 18 mg/kg to 23 to 66 mg/kg within 3 years. Oxalate extractable Fe, Al, and P was determined for all treatments in both soils and used to calculate phosphorus saturation (PSIox ). PSIox values from sand treated with one organic fertilizer source were significantly higher than measured in other treatments, indicating future risk of P loss with repeated applications of this organic fertilizer.